2023
DOI: 10.1101/2023.11.28.568901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulators of health and lifespan extension in genetically diverse mice on dietary restriction

Andrea Di Francesco,
Andrew G. Deighan,
Lev Litichevskiy
et al.

Abstract: SummaryCaloric restriction (CR) delays aging and extends healthy lifespan in multiple species. Alternative forms of dietary restriction (DR) such as intermittent fasting (IF) have drawn significant interest as a more sustainable regimen, but the landscape of longevity-promoting dietary interventions remains largely unexplored. Identifying the most robust, efficacious, and experimentally tractable modes of DR is key to better understanding and implementing effective longevity interventions for human healthspan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 81 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Surprisingly based on previous literature suggesting CR works poorly when initiated late in life (25), both studies found that mice placed on either 20% or 40% CR lived significantly longer, while intermittent fasting did not significantly extend lifespan (23, 24). Calculating healthspan from the longitudinal frailty data, we found that 20% and 40% CR, but not intermittent fasting, significantly extended healthspan ( Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Surprisingly based on previous literature suggesting CR works poorly when initiated late in life (25), both studies found that mice placed on either 20% or 40% CR lived significantly longer, while intermittent fasting did not significantly extend lifespan (23, 24). Calculating healthspan from the longitudinal frailty data, we found that 20% and 40% CR, but not intermittent fasting, significantly extended healthspan ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…This was somewhat difficult, as several studies we examined collected healthspan data either at single time points or from only a subset of animals whose lifespans were also determined. Fortuitously, two recent studies collected longitudinal frailty data and determined the lifespan of genetically heterogeneous Diversity Outbred (DO) mice on one of several different diet regimens (23, 24). In these studies, mice were placed on ad libitum (AL) diet, intermittently fasted (1D and 2D represent groups that fasted once or two consecutive days per week in the first study, respectively, while IF1 and IF2 represent mice that were fasted either one or two days per week in the second study, respectively), or placed on either a 20% or 40% CR diet (CR20 and CR40, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, we note that male and female mice on the folate-limited diet maintained their weight better as they aged than their counterparts on the folate-replete diet (Figure 2), likely through increased adiposity. A recent study identified these phenotypes as top predictors for positive effects on health and lifespan in genetically diverse mice on various dietary restriction diets (Di Francesco, A. et al, 2023).…”
Section: Reduced Anabolism Is Common Among Pro-longevity Intervention...mentioning
confidence: 99%